Theme and Rhythmic Structure in The Poem I Hear America Singing by Walt Whitman - Tazky Aulia Rahmah (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2026)
“I Hear America Singing” by Walt Whitman is a poem of patriotism with diversity in the landscape of America. The aim of this journal is to interpret the motifs and rhythmic forms employed by Whitman in this poem. In the first place, what the paper would like to study are themes in the poem. What is the poem about? The poem is about various types of professions or workers and their occupations in America. The poem ends with a cheerfully inaccurate portrayal of the United States as "a proud and great Republic Courted by all," one that fuses people from different parts of world with their sweat and synergy. This journal will parse the rhythmic structure of poetry. A strong pattern of repetition and rhythm is used to construct musical effects in Whitman’s poetry. A steady and rhythmic rhythm epitomizes hard work and the flow of daily life. Repetition by also stands to echo sameness and commonality among all the persons presented throughout the poem. By focusing on theme and scansion, the journal will ask you to explore just what it is that Whitman wanted readers to pay attention to regarding his words in the poem "I Hear America Singing." ‘The poem expresses Whitman’s love and admiration for America’s mass democratic society, while pressing on importance- of laboring, continuity, and all inclusive spirit with which you have to progress hand in hand. Through theme analysis and rhythmic structure, the journal will help readers understand the key messages communicated by Whitman in the poem "I Hear America Singing." The poem demonstrates Whitman's love and appreciation for America's diverse society and emphasizes the importance of hard work, continuity, and a collective spirit for achieving progress together. Keywords: Poem, Theme, Rhythm